2016
DOI: 10.1177/1753193416674929
|View full text |Cite
|
Sign up to set email alerts
|

Successful conversion of wrist prosthesis to arthrodesis in 11 patients

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 15 publications
0
30
0
2
Order By: Relevance
“…The Maestro™ WRS has demonstrated uncomplicated conversion to TWF [25, 26, 33, 34]. A recent study revealed that the outcome of TWF after a failed TWA is comparable to those after primary TWF [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The Maestro™ WRS has demonstrated uncomplicated conversion to TWF [25, 26, 33, 34]. A recent study revealed that the outcome of TWF after a failed TWA is comparable to those after primary TWF [35]. …”
Section: Discussionmentioning
confidence: 99%
“…There are only a few articles reporting on the outcomes of treatment or "salvage" of a failed TWA. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The aim of this study is to undertake a systematic review of the available literature to assess the clinical effectiveness of the different strategies that can be utilized in this challenging situation. The following research questions forming the basis for this review are: Does physical function improve with surgical management of the failed wrist arthroplasty?…”
mentioning
confidence: 99%
“…TWF is unchanged a method of choice for primary treatment of traumatic and non-traumatic wrist OA especially for young and younger patients with high claims in their work and leisure [48,120] as well as a reliable salvage option after a failed 4CF, PRC, and TWA ( Fig. 7 A-E) [81,121]. However, patients are limited in performing their activities of daily living.…”
Section: Function Universal 2 Re-motion Maestromentioning
confidence: 99%